Characteristics of autologous peripheral blood stem cells collection over a one-year period - Gorana Ahmetović-Karić; Elma Ćatović-Baralija; Alma Sofo-Hafizović (Medicinski glasnik, 2020)
Aim: To present characteristics of collecting autologous peripheral blood stem cells over a one-year period with an emphasis on efficiency and safety. Methods: A retrograde analysis of 24 leukapheresis in 20 adult patients with malignant haematological diseases in the Blood Transfusion Institute of the Federation of Bosnia and Herzegovina in Sarajevo, was done. Cell separators Amicus and Spectra Optia were used for collection procedures. Results: The patient's age ranged from 27 to 65 years. Target cells were collected in one procedure in sixteen patients, while in four patients they were collected in two procedures. The mean CD34+ collection efficiency was 57.7%. The median number of CD34+ cells and percentage of CD34+ cells in the products were 5.52x10e6/kg (range 3.28-9.00) and 1.57% (range 0.96-2.91). A strong positive correlation was found between the number of CD34+ cells in peripheral blood on the apheresis day and the amount of CD34+ cells collected in the products (r s =0.73). A total of 95% of patients collected the amount of ?3x10e6/kg and 55% of ?5x10e6/kg CD34+ cells for a single transplant. A decrease in platelet count, haemoglobin and haematocrit values after the procedure was not significant. Potassium decrease showed statistical significance (p<0.000). Adverse events occurred during one procedure (4.2%). Conclusion: A low number of adverse events and good collection efficiency with adequate patient monitoring, indicate that leukapheresis is a safe procedure that is successfully used in the autologous transplantation process in the treatment of malignant haematological diseases.
Keywords: CD34; hematopoietic stem cells; leukapheresis